Tattoos in ancient Maghreb between symbolism and rituals (original research and roles). - rachi, nadjwa (Journal of Social Sciences and Humanities, 2024)
Tattoos represent a form of popular artistic expression that has received little attention in historical studies. At the same time, it is unique in Maghreb popular culture, which has led many to tattoo their bodies as a form of decoration or popular treatment within the framework of its practice within social and cultural dimensions that are linked to the beliefs and customs inherited from its practitioners. In this research paper, we will try to shed light on this custom, which was practiced in the countries of ancient Morocco, starting from the rocky scenes in which some suggestions were discussed on the tattoos' existence among the inhabitants of the region, and the forms circulated among them, especially those engineering symbols and signs that are still vague and unclear, in an attempt to clarify the purpose, is it religious (ideological) or medical (remedial) ?.